Penggunaan Pembelajaran Contextual Teaching And Learning (CTL) pada Pembelajaran Matematika Siswa Kelas III di SDN Karangwono 01 Pati - Siti Nur Khomsah; Nur Fajrie; Sri Surachmi W (Departement of Mathematics Education, 2023)
Students do not understand the material and the students' low interest in learning mathematics, low mastery of material about mixed arithmetic operations involving multiplication and division and low student learning outcomes in mathematics. This is caused by, the teacher in providing an understanding of the concept is not in accordance with the abilities of students, the use of learning models and methods that are less varied, the teacher does not provide motivation, and is too quick to provide learning material. This research is to analyze various applications of Contextual Teaching Learning (CTL) learning in mathematics learning. The method used in this research is qualitative. The results of the research are in the process of delivering the subject matter students enthusiastically pay attention to the teacher's explanation and do mixed calculations with pleasure, and in accordance with what they encounter in everyday life. CTL is an appropriate learning model to increase learning motivation in class and according to the characteristics of students who tend to be passive.